BECOMING DOMESTIC IN HESIOD'S WORKS AND DAYS. (December 2020) - Radcliffe, Ben
Abstract : The work of Gilles Deleuze is populated by literary and artistic figures who become stuck, confined, and exhausted: he has written about the characters of Samuel Beckett, for instance, who are incapacitated by a compulsion to count and sort; Sacher-Masoch's protagonists, who share their author's eponymous desire to defer endlessly the sexual act; and the notorious figures in the paintings of Francis Bacon, determined but unable to escape the confines of their own bodies. What accounts for Deleuze's interest in scenes of stasis and immobility? These figures, and others like them, seem to appeal to Deleuze precisely because their corporeal limitations coincide with intense and inscrutable affects, as if Spinoza's maxim, 'we do not even know what the body can do', is true especially when the body's capacities appear most restricted. This is an aspect of Deleuze's thought that complicates his reputation as a philosopher of limitless becoming, movement, and synthesis.